(3HTQi GdcFjH HdbGA GdMHjHs - (3GdSjhWj GdNVjQj, CHh GdaVd, LdGd GdOjf, YHO GdQMef Hf CHj HcQ Hf eMeO, J (B911 (3gs
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B... (3hHYO gPG LRA(B... (3dNUJg ef cJGHj GdcHjQ GdPj CdaJg aj CMhGd GdHQRN bUQJg Ydi GdHTQi eeG jdbGg GdeDef YfO ehJg haj bHQg(B...s
(3BNQgG (B:s
(3hGYde HCf GdfaS dG QGMI dgG Ohf eaGQbJgG GdLSO(B... (3aEPG GdehJ MceI hQMeI(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B2(3, U(B82s
(3GdCYdGe(B: (3L(B3(3, U(B301s
(3cTa GdXfhf(B: (3L(B1(3, U(B246s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdMOjK hGdeUWdMs